The Relationship between School Socioeconomic Composition and Academic Achievement in Turkiye - Mahmut Özer; Eren Suna (Journal of Economy Culture and Society)
The socioeconomic distribution of students influences school contexts and learning processes. In this manner, a school’s socioeconomic composition has the remarkable potential to shape school climate. This study examines the relationship socioeconomic status (SES) at both the student and school levels has with academic achievement for the first time in Turkiye with regard to academic and vocational tracks. High-stake assessment data of more than 1.4 million students over the last 10 years have been analyzed using two-level hierarchical linear modelling (HLM). The results show parents’ education level to be a significant predictor for both academic and vocational tracks, while family income significantly predicts academic achievement just in regard to vocational track. The results highlight both students’ and peers’ SES to be significantly related to their academic achievement. Additionally, parents’ education level is a stronger predictor of achievement than family income level. The results also emphasize the importance the recent improvements and academic support programs from the Ministry of National Education (MoNE) have had in alleviating achievement gaps among schools.